PERINATAL REPERCUSSIONS OF CONGENITAL SYPHILIS IN NEWBORNS FROM A HABITUAL RISK MATERNITY HOSPITAL IN 2020 - Gropillo, Carolina Gonçalves; Shimizu, Letícia; Simão, Melissa Hissami; Azulay, Caroline Wainstein; Ornellas, Marcela Reis Rico; Serra, Mayco José Reinaldi; David, Maria Luisa Diaz Cunha; Rullo, Vera Esteves Vagnozzi (Seven Editora, 2025)
Objective: To evaluate the perinatal repercussions of newborns (NB) affected by congenital syphilis (CS) in comparison with the profile of NB not exposed in the same period of time. Methodology: This is a historical cohort study carried out through the collection of maternal and neonatal data obtained through the Birth Book of the Municipal Maternity of São Vicente, a habitual risk maternity hospital in the Metropolitan Region of Baixada Santista - São Paulo, during the year 2020. The exposure group was characterized by NB affected by congenital syphilis and the control group by NB not exposed. Results: The exposure group is composed of 45 NB with notified and confirmed CS, and 80% of them have low VDRL titers. In the analysis of maternal variables, 82.22% of the mothers are between 19 years old and under 35 years old; 66.67% had less than 6 prenatal consultations; and only 33.33% had a cesarean section. Neonatal variables show that 75.56% of the NB were born with a gestational age (GA) between 37 weeks and 41 weeks and 6 days. Among the NB analyzed, 28.89% were underweight; 20% were classified as SGA; and of the NB classified as SGA, 55.56% were proportional. In addition, 44.44% had small stature for GA and 26.67% were classified as small PC for GA. Regarding the Apgar score in the 1st minute, 24.44% had scores less than or equal to 7 and 71.11%, between 8 and 10; in the 5th minute, 88.89% received a score between 8 and 10. After birth, 73.33% of the NB were sent to rooming-in and 17.78% to the neonatal ICU. Conclusion: The presence of CS was related to a higher incidence of unfavorable neonatal outcomes, when compared to those not exposed, in the variables prematurity, low weight for GA, 1-minute Apgar score less than 7 and referral to the neonatal ICU.DOI: https://doi.org/10.56238/sevened2024.037-204